1963
DOI: 10.21236/ad0408761
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Random Phase Errors on the Angular Resolution of Synthetic Aperture Radar Systems

Abstract: The influence of random phase errors on the angular resolution of a focused synthetic aperture radar system is treated. The principal measure of performance has been taken as the mean envelope power at the system output. This system output power is evaluated exactly, although not in closed form, based on the following reasonable assumptions: (1) the real beam pattern is Gaussian; (Z) the random phase error is essentially a geometry independent ergodic process with a Gaussian amplitude distribution and zero mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1967
1967
1981
1981

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…At any rate, all that is required for estimation of the accuracy of the calculated results is a comparison of u:+ua2 with 1.0. As demonstrated by applications here and elsewhere [6], [7], values of u,2 and ua2, which render the analyses useless, are of little interest in practical antenna design, since they result in high sidelobes (> -10 dB) or low gain in all cases, except when correlation among phase errors of neighboring elements in the array is high [7].…”
Section: Range Of Applicationmentioning
confidence: 93%
See 2 more Smart Citations
“…At any rate, all that is required for estimation of the accuracy of the calculated results is a comparison of u:+ua2 with 1.0. As demonstrated by applications here and elsewhere [6], [7], values of u,2 and ua2, which render the analyses useless, are of little interest in practical antenna design, since they result in high sidelobes (> -10 dB) or low gain in all cases, except when correlation among phase errors of neighboring elements in the array is high [7].…”
Section: Range Of Applicationmentioning
confidence: 93%
“…However, it was pointed out previously that a binary autocorrelation coeffi-1 cient greatly reduces the size of the lengthy summations in the analytical results. Nevertheless some special choices for ,,fi (no-error amplitude distribution and antenna element pattern) still provide tractable results with other realistic autocorrelation coefficients [7]. However, if the summations are still too lengthy to be cheaply computed, an integral approximation, or lower order sum, may be used with some success [ 6 ] .…”
Section: Range Of Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…The signal-tothermal-noise ratio (S/N) increases in proportion as the PLL noise bandwidth becomes narrower. Develet [5] found that the PLL unlocks if loop S/N falls below 1.34 dB. At this threshold level the rms phase error is calculated to be 1.0 rad.…”
Section: Beacon Link Parameter Designmentioning
confidence: 94%